The effect of organizational justice and spiritual value on employee engagement and turnover intention / Aditya Herwanto and Abdul Hakim - Herwanto, Aditya; Hakim, Abdul (2022)
This study aims to test and analyze the influence of organizational justice and spiritual value on employee engagement and turnover intention. The population in this study were doctors, paramedics and other non-paramedics at The Unimus Dental and Oral Hospital. Considering the population is only 50 people, the whole sample was used, so this study is a census study. The data source used is primary data obtained from respondents who answered a questionnaire. The data analysis method used is descriptive analysis of variables and partial least square test. The results of this study are 1) organizational justice and spiritual value affect employee engagement, 2) spiritual value and employee engagement are influential in reducing turnover intention, 3) Employee engagement can play a role in mediating organizational justice and spiritual value against turnover intention. The results of this research show that to minimize the turnover intention, there should be efforts on the part of hospital management to provide fairness to its employees, such as the ability to adjust the workload in men and women, the fair attitude of supervisors, the similarity in providing assessments, the importance discussing work results and fair attitudes given by employees in expressing opinions. Other efforts can also be seen from the application of spiritual values at work, namely providing service with earnestly and being courteous to the community or patients.